Implementasi Pembelajaran Kewirausahaan Berbasis Pengalaman Langsung dalam Mengembangkan Keterampilan Sosial Anak Usia Dini - Ningtiyas, Wulandhari Arum; Falera, Ana (UIR PRESS, 2026)
This study is motivated by the importance of early childhood social skills as a provision for interacting, collaborating, and communicating with the social environment. This study aims to describe the planning, implementation, and evaluation of entrepreneurship learning in familiarizing children aged 5-6 years with social skills. This study uses a descriptive qualitative approach implemented at TK Alam Mutiara Umat Tulungagung with research subjects consisting of 1 principal, 3 group B teachers, and group B students. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used data reduction, data presentation, and drawing conclusions. The results of the study indicate that entrepreneurship learning is implemented through various activities based on direct experience, such as buying and selling and cooking classes that are integrated into daily learning. Children's involvement in these activities contributes to the development of social skills, especially in communication skills, cooperation, social interaction, and self-confidence. The research findings indicate that social skills habituation is not only formed through Market Day activities as found in many previous studies, but also through various entrepreneurial activities carried out on an ongoing basis. Thus, entrepreneurship learning contributes as a means to familiarize early childhood social skills through authentic learning experiences integrated into daily learning activities.